EXPERIMENTAL AND NUMERICAL SIMULATION STUDY OF INDUCTOR FAULT BY INVESTIGATING WINDING CONTOUR - KHOO, BOO KEAN (2015)
Multiple layer winding are typically with higher losses compare to singular layer. Winding design and contour are important factors in inductors design with multiple layer technique, since inductor design with multiple stacking are prone to proximity effect. Thermal stress points in the inductor winding can cause insulation deterioration and ageing effect, leading to winding faults. The contour design and its influence on the winding fault of an inductor were investigated with the aim of selecting an optimum winding contour design. In this dissertation, a winding fault model was developed and behaviors of inductors with different winding contours are investigated using the Finite Element Method (FEM) based on 2-Dimension model. The fault model developed is able to calculate and determine the optimal combination of parameters corresponding to various contour designs that would result in minimum winding loss. Inductors with different winding contours have different thermal envelopes and the geometry with the slowest thermal transition has fewer thermal stress points potentially reducing winding fault at the conductor.